2011
DOI: 10.1073/pnas.1113921108
|View full text |Cite
|
Sign up to set email alerts
|

Conformational plasticity of glycogenin and its maltosaccharide substrate during glycogen biogenesis

Abstract: Glycogenin initiates the synthesis of a maltosaccharide chain covalently attached to itself on Tyr195 via a stepwise glucosylation reaction, priming glycogen synthesis. We have captured crystallographic snapshots of human glycogenin during its reaction cycle, revealing a dynamic conformational switch between ground and active states mediated by the sugar donor UDP-glucose. This switch includes the ordering of a polypeptide stretch containing Tyr195, and major movement of an approximately 30-residue "lid" segme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
41
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 23 publications
5
41
0
Order By: Relevance
“…Because residue 150 is variable, residues 149 -151 are herein named as the NXG motif to simplify its description. Crystallographic studies found the NXG motif to form a part of the ligand-binding pocket: NXG of Neisseria meningitidis LgtC surrounds the "C1" of the donor ligand (37), and the NXG of human glycogenin-1 interacts with the hydroxyl groups of "C2" and "C3" of Glc (32). Molecular modeling of WciN␣ using PHYRE2 (38) also predicted the NXG motif to form a ligand-binding pocket.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because residue 150 is variable, residues 149 -151 are herein named as the NXG motif to simplify its description. Crystallographic studies found the NXG motif to form a part of the ligand-binding pocket: NXG of Neisseria meningitidis LgtC surrounds the "C1" of the donor ligand (37), and the NXG of human glycogenin-1 interacts with the hydroxyl groups of "C2" and "C3" of Glc (32). Molecular modeling of WciN␣ using PHYRE2 (38) also predicted the NXG motif to form a ligand-binding pocket.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the mutation at residue 150 is present in both German strains and is located within a highly conserved region. For instance, residues 148 -152 of WciN␣ are conserved in human glycogenin-1, except for residue 150 (FNAGV versus FNSGV) (32). Because residue 150 is variable, residues 149 -151 are herein named as the NXG motif to simplify its description.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glycogenin is a member of the GT8 family of glycosyltransferases with a GT-A architecture containing an N-terminal catalytic domain with a single Rossmann fold that operates as an obligate dimer (12)(13)(14). The core catalytic domain is followed by a C-terminal extension of variable length and undefined structure.…”
mentioning
confidence: 99%
“…Histidine tag-associated modifications such as gluconoylation will also be lost following TEV cleavage. Intact mass measurements can be used to monitor deliberate modifications of the protein, such as biotinylation [26], reductive methylation [27], glycosylation [28], incorporation of SeMet or isotopically-labelled amino acids, or the removal of the tag by TEV cleavage. In all cases where a mass discrepancy cannot be unequivocally accounted for, the expression clone is (re)-sequenced.…”
Section: Intact Mass Analysis Is Used To Reveal Expected/unexpected Pmentioning
confidence: 99%